The impact of social capital-based selection practices on talent management: evidence from telecom MNCs in Bangladesh - Syed, Monirul H. *; Mohammad Jasim, U. *; Fujimoto, Yuka *; Toh, Seong-Yuen * (Inderscience, 2021)
The purpose of this paper is to explore how social capital-based selection practices influence talent management (TM) in multinational companies (MNC). To date, little is known about this relationship. Empirical data were collected from 12 managers of three telecommunication firms in Bangladesh using in-depth interviews. Our study found a significant influence of social capital-based selection practices on TM. We found that the relational and cognitive dimensions of social capital were the major drivers of selection practices that influenced a talent search process. Trust and cultural norms within networking relationships affected TM through shared narratives, codes, and language. Therefore, the role of existing human resource management (HRM) system for selection practices was found inadequate without the integration of social capital. For practical implications, upper-level managers used social capital-based selection practices beyond HRM systems that were deemed pragmatic in selecting the right candidates for positions in organisations favouring intra-group homogeneity.